The Indicators of X-ray Density of Bone Tissue after using the Different Surgical Protocols of Dental Implantation - Tsuperiak Сергій Степанович; Mochalov Юрій Олександрович (Actual Dentistry, 2023)
The purpose of the work: to establish experimentally the influence of various surgical preparation protocols for implantation canal on the radiological density of bone tissue. Materials and methods. On 8 samples of porcine ribs without water cooling the 4 implantation channels were formed - one with a final surgical drill at a speed of 1000 rpm; another – at 300 rpm, the third – at 50 rpm and one channel was formed by a bone condenser (all tools from "UXIF" and "RS Kit", "Dentium" (Korea), torque = 35 NЧcm. X-ray examination of bone tissue was performed in a cone-beam computer tomograph, image analysis and determination of the relative density of bone tissue - in the computer program "IRYS Viewer" ("MyRay", Italy). Results and discussion. The relative radiological density of bone tissue differed a little during the preparing of bone tissue at speeds of 1000 rpm and 300 rpm. And it was more pronounced when using the bone condenser at a speed of 100 rpm and a conventional surgical drill at a speed of 50 rpm. Preparation of the bone samples at high speed (1000 rpm) caused a slight decrease in tissue density, was observed by 5.69%, the median = 2.69%. The average density of bone tissue decreased by 43.57 dHu (М=19.00 dHu). At a speed of 300 rpm, a slight decrease in tissue density by 0.08% (М=0.43%) was observed. The average density decreased by 0.65 dHu (M=3.00 dHu). During bone preparation with a bone condenser at a speed of 100 rpm an increase in tissue density was observed by 29.50% (М 33.26%), in numerical terms, bone tissue density increased by 275.04 dHu (М=274.00 dHu). Preparation at a speed of 50 rpm led to an increase in the average x-ray tissue density by 38.81% (M=40.21%). In general, the density of bone tissue increased by 240.48 dHu (М 225.00 dHu). The slow rate of bone tissue preparation which maybe performed without water cooling, even with the use of a clockwise finishing surgical drills, avoids micro-fractures of the bone beams and promotes bone tissue compaction (condensing). Conclusion. Therefore, the use of different protocols for the preparation of the implantation canal in the bone tissue causes statistically probable changes in the radiological density of the bone tissue. Thus, the preparation of bone tissue at a speed of 1000 rpm causes a slight decrease in the density of bone tissue near the implantation hole – 2.69% which was statistically improbable. Preparation of bone tissue at a speed of 300 rpm does not cause significant and statistically significant changes in the radiological density of bone tissue near the implantation channel. The use of bone condensers at a speed of 100 rpm causes a statistically significant increase in the radiological density of bone tissue by 33.26%. A similar effect was achieved when preparing bone tissue with a surgical finishing cutter clockwise at a speed of 50 rpm – the radiological density increased by 40.21% which was a statistically significant result.